Personnel Protective Equipment: Forgotten Protocol, Invigorated by COVID-19 - Prabhu, Namdeo (2021)
Objective: To make the readers cognizant about the use of Personnel Protective Equipment (PPEs) and infection control practices which should always form a part of basic patient management and not arise with every emerging disease. Material and Methods: Authors personal clinical experiences and existing literature were summed up to infer relevant information related specifically to dentistry. A comprehensive review was done for the last 15 years in an attempt to explain the current state of understanding on the topic. Results: The authors have tried to compile the most probable reasons as to why PPEs have been a forgotten protocol, which can be enumerated as follows: decreased awareness, financial issues, boredom and lethargy, time constraints, unavailability, carelessness, and burnout due to long procedure and patient feeling discomfort/offended. Conclusion: COVID-19 being highly infectious, a dental clinic is a potential and genuine point of source for many new infections, and no confabulation is less to underline the importance of using PPEs during this pandemic or even otherwise.